Extraction of bioactive compounds from plant materials using combination of various novel methods: A review - Jha, Avinash Kumar; Sit, Nandan (Trends in food science & technology, 2022)
The first step in the isolation and purification of bioactive compounds from plant material is extraction. Extraction of secondary metabolites such as phenolic acids and flavonoids is difficult due to their insoluble nature. While conventional extraction methods such as Soxhlet, heat reflux, and maceration are successful procedures in the extraction of bioactive compounds and the equipment involved in these methods are distinct from each other. An appropriate extraction technique that balances product quality, process efficiency, production costs, and environmentally acceptable methods should be used for the extraction of bioactive compounds from plant tissues. The application of innovative extraction methods in the food industries has been extensively investigated, due to increased consumer expectations for greener options that do not include hazardous chemicals, as well as industry concerns about sustainable, nontoxic extraction techniques. Innovative technologies, such as high hydrostatic pressure (HHP), ultrasound (US), pulsed electric field (PEF), supercritical fluid (SF), and others, are increasingly replacing the conventional methods. The use of novel and combined novel technologies increases extractability, resulting in yields with higher extraction rates. It also yields lower impurities in the final extract and preserves thermo-sensitive compounds, uses different inorganic solvents, and consumes low energy. The purpose of the present review is to evaluate the efficiency of the different conventional, novel, and combined novel technologies involved in the extraction of bioactive compounds from plant materials. [Display omitted] •The various conventional techniques for extraction of bioactive compounds are reviewed.•The paper also reviewed the various novel technologies for extraction of bioactive compounds.•The focus of the paper is combined novel technologies for extraction of bioactive compounds.•Efficiency of the extraction process can be increased by combining two technologies.